Pengaruh Permainan Magic Box (Kotak Ajaib) terhadap Kemampuan Berbicara Anak di Tk Pertiwi Moluo Kecamatan Kwandang Kabuapaten Gorontalo Utara - Nurul Amalia Minatin; Nunung Suryana Jamin; Yenti Juniarti (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to analyze the effect of implementing the Magic Box game on the speaking abilities of Group B children at Tk Pertiwi Moluo Kindergarten, Kwandang District, Gorontalo Utara Regency. The study employed a quantitative approach with a pre-experimental design, specifically a one-group pre-test-post-test design. The study sample consisted of 32 Group B children. Data analysis was conducted using statistical data processing. Data were collected through observation and assessment of children's abilities before and after the game intervention. The analysis results indicated a significant improvement in children's speaking abilities following the implementation of the Magic Box game. The pre-test average score had a median of 19.00 with a standard deviation of 1.721, while the post-test average score increased to 35.53 with a standard deviation of 2.347. Children's abilities improved from an initial average of 19.5 to 35.53 after the intervention. Based on the paired test table, the significance value (2-tailed) of 0.000 < 0.349 indicated that H0 was rejected and H1 was accepted, thus supporting the hypothesis that the Magic Box game positively influenced the speaking abilities of Group B children at Tk Pertiwi Moluo Kindergarten, Kwandang District, Gorontalo Utara Regency.